Implementasi Kaizen Untuk Mengurangi Waste Pada Produksi Pembuatan Pintu (Studi Kasus di CV. Romelan Jaya Paint) - Hartono, Hartono; Rival, Muhammad (Program Studi Teknik Industri Universitas Muhammadiyah Tangerang, 2023)
CV. Romelan Jaya Paint is a company engaged in the furniture and furniture industry. Problems contained in the CV. Romelan Jaya Paint, namely there is still waste in the production process so that the desired production results have not been achieved by the company. The material area becomes central in improving the production process. This study uses the Kaizen PDCA (Plan, do, check, action) method to solve a problem and is assisted by a fishbone diagram to find the root cause of the problem. So that waste can be eliminated and processing time in the production process. Prior to the repairs, productivity results from January to December 2021 only reached an average of 85%. After making improvements for 3 months from March – May 2022, production output increased to 97.43 so that there was an increase of 12.43%). Productivity has increased from an average of 13 pcs doors per day, now to 15 pcs. With this, the target in a month is to reach 100% according to company standards in March and April 2022.Keywords: Waste, Kaizen, PDCA, Fishbone diagram, Productivity.